ANALISIS PENGARUH KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi pada Pengguna Fladeo Ladies di Jakarta) - Nababan, Jelita Safitri; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2019)
Nowadays, the development of shoe industry has been very rapid and many shoes brands that have been offered both domestically and abroad, one of which is brand Fladeo. With the many choices offered, consumers are also increasingly critical in making purchasing decisions. In this case there are several factors that can influence consumer purchasing decisions such as product quality and word of mouth. The purpose of this research is to analyse the influence of product quality and word of mouth againts the purchasing decision of Fladeo and brand image as an intervening variable.The population in this research is female consumers in the city of Jakarta and there are 130 respondents as the sample research. Sampling in this research using non-probability sampling methods and purposive sampling techniques. This research using Structural Equation Modeling (SEM) analysis technique which is estimated with AMOS 22.0.The results of this research shows that product quality and word of mouth has a positive and significant effect againts brand image and purchasing decisions, then the brand image has a positive effect againts purchasing decisions.